Geochronology, geochemistry, and petrogenesis of the Kezijiaer gabbros, southern Chinese Altai: Evidence for ridge subduction. (5th February 2020) - Wang, Zuopeng; Li, Yongjun; Yang, Gaoxue; Zhang, Yuling; Li, Hai; Zhao, Yumei; Lindagato, Philemon
Abstract : The Chinese Altai as a key part of the Central Asian Orogenic Belt is characterized by wide outcrops of Palaeozoic granitoids and minor mafic plutons. It is widely accepted that Devonian ridge subduction played an important role in the tectonic evolution of the Chinese Altai. However, Carboniferous magmatism related to ridge subduction has received little attention. Here, we report zircon U–Pb age and whole‐rock geochemistry of the Kezijiaer gabbros in the southern Chinese Altai, aiming to elucidate their emplacement age and petrogenesis and tectonic setting. Laser ablation inductively coupled plasma mass spectrometry zircon U–Pb dating shows that the Kezijiaer gabbros were emplaced in the Early Carboniferous with a crystallization age of 348 ± 3 Ma (mean square of weighted deviates = 0.46). Geochemically, the Kezijiaer gabbros exhibit low SiO2, high MgO, Fe2 O3, Ni, and Cr concentrations, as well as enrichments of light rare earth elements and large‐ ion lithophile elements (e.g., Rb, Ba, Th, and U) relative to high‐field‐strength elements and heavy rare earth elements. Meanwhile, they have high TiO2, Nb/Ta, Zr/Hf, and Ti/V and low La/Yb values. These features show that the gabbros share geochemical signatures of both island arc basalt and mid‐ocean ridge basalt. Together with low La/Sm, Sm/Yb, and Dy/Yb ratios, it is suggested that the Kezijiaer gabbros mainly originated from partial melting of a spinel lherzolite mantle wedge metasomatized by subduction‐related fluids and sediment melts with input of asthenospheric components, subsequently followed by fractional crystallization of olivine and clinopyroxene. Taking into account regional geology and published data, we argue that an Early Carboniferous ridge subduction regime responsible for the Kezijiaer gabbros might have also exerted a pivotal role in the tectonic evolution processes of the Chinese Altai in the Palaeozoic.